À la manière de l’abeille ... Gaston Bachelard, cosmogonie et imagination - Solares, Blanca (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2020)
Starting from some myths traced by the anthropologist and writer José María Arguedas, one of the greatest exponents of 20th century Latin American literature, this article aims to deepen the relationship between the symbolic language of the pre-Columbian conception of nature and the theory of material imagination of Gaston Bachelard, a close reader of romantic literature. One of the main effects of the period of the highest industrial development in the West was that of having transformed nature into an exploitable resource of generalized and unfair consumption. The intention of the following lines is to highlight some of the contributions of Bachelard’s theory of imagination to the understanding of the structure of mythical consciousness and, at the same time, to show the points of coincidence of traditional conceptions of the pre-Columbian cosmos with the bachelardian poetics of nature. A set of cosmological and ontological aspects that call into question the categories of the patriarchal and colonialist West. Keywords: Bachelard, imagination, ecology, anthropology, cosmovision